RETRACTED ARTICLE: Combination therapy with Nab-paclitaxel and the interleukin-15 fused with anti-human serum albumin nanobody as a synergistic treatment for colorectal cancer. Issue 1 (1st January 2022) - Wu, Lipei; Wang, Weiwei; Tian, Jiale; Qi, Chunrun; Cai, Zhengxin; Yan, Wenhui; Xuan, Shihai; Shang, Anquan
Statement of Retraction: We, the Editors and Publisher of the journal  Bioengineered, have retracted the following article: Lipei Wu, Weiwei Wang, Jiale Tian, Chunrun Qi, Zhengxin Cai, Wenhui Yan, Shihai Xuan & Anquan Shang. Combination therapy with Nab-paclitaxel and the interleukin-15 fused with anti-human serum albumin nanobody as a synergistic treatment for colorectal cancer. Bioengineered. 2022; 13(1): 1942-1951. DOI: 10.1080/21655979.2021.2023997 Since publication, it has been brought to the attention of the Editors and Publisher that this article includes substantial similarity with another published article: Hsu, F-T,  Tsai, CL,  Chiang, I-T, Lan, K-H, Yueh, P-F, Liang, W-Y, Lin, C-S, Chao, Y, & Lan, K-L. Synergistic effect of Abraxane that combines human IL15 fused with an albumin-binding domain on murine models of pancreatic ductal adenocarcinoma.  Journal of Cellular and Molecular Medicine . 2022; 26: 1955– 1968. doi:10.1111/jcmm.17220 The previous article is not referenced at any point within the Bioengineered article. Further investigations conducted by the Publisher have raised significant concerns about the integrity of the data and results reported in the article due to the choice of in vivo and in vitro models, as well as the lack of original data to support the quantifications presented. When approached for an explanation, the authors were unable to provide their original data or any necessary supporting information. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.